Modelling an alkenone-like proxy record in the NW African upwelling - X. Giraud (Biogeosciences, 2006)
A regional biogeochemical model is applied to the NW African coastal upwelling between 19° N and 27° N to investigate how a water temperature proxy, alkenones, are produced at the sea surface and recorded in the slope sediments. The biogeochemical model has two phytoplankton groups: an alkenone producer group, considered to be coccolithophores, and a group comprising other phytoplankton. The Regional Ocean Modelling System (ROMS) is used to simulate the ocean circulation and takes advantage of the Adaptive Grid Refinement in Fortran (AGRIF) package to set up an embedded griding system. In the simulations the alkenone temperature records in the sediments are between 1.1 and 2.3°C colder than the annual mean SSTs. Despite the seasonality of the coccolithophore production, this temperature difference is not mainly due to a seasonal bias, nor to the lateral advection of phytoplankton and phytodetritus seaward from the cold near-shore waters, but to the production depth of the coccolithophores. If coretop alkenone temperatures are effectively recording the annual mean SSTs, the amount of alkenone produced must vary among the coccolithophores in the water column and depend on physiological factors (e.g. growth rate, nutrient stress).